2021
DOI: 10.1101/2021.03.09.434591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomics-based determination of double stranded RNA interactome reveals known and new factors involved in Sindbis virus infection

Abstract: Viruses are obligate intracellular parasites, which depend on the host cellular machineries to replicate their genome and complete their infectious cycle. Long double stranded (ds)RNA is a common viral by-product originating during RNA virus replication and is universally sensed as a danger signal to trigger the antiviral response. As a result, viruses hide dsRNA intermediates into viral replication factories and have evolved strategies to hijack cellular proteins for their benefit. The characterization of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(158 reference statements)
0
1
0
Order By: Relevance
“…Notably, using this in vitro dicing assay, they found that aviD is more resistant to LGP2 [40]. Whether other cofactors of Dicer, such as PKR-associated activator (PACT), protein kinase RNA-activated (PKR) and adenosine deaminases acting on RNA 1 (ADAR1), modulate the Dicer's ability to cleave dsRNA in vivo needs to be further investigated [68][69][70].…”
Section: Other Than Truncated Dicer Full-length Dicer Can Also Proces...mentioning
confidence: 99%
“…Notably, using this in vitro dicing assay, they found that aviD is more resistant to LGP2 [40]. Whether other cofactors of Dicer, such as PKR-associated activator (PACT), protein kinase RNA-activated (PKR) and adenosine deaminases acting on RNA 1 (ADAR1), modulate the Dicer's ability to cleave dsRNA in vivo needs to be further investigated [68][69][70].…”
Section: Other Than Truncated Dicer Full-length Dicer Can Also Proces...mentioning
confidence: 99%